A new species of Physocyclus (Araneae: Pholcidae) from Mexico - Jiménez, Maria-Luisa; Palacios-Cardiel, Carlos (Zootaxa, 2013)
The genus Physocyclus (Pholcidae) is widely distributed in North and Central America, with the exception of the Antilles (Platnick 2013). Physocyclus species are found in various environments, including xeric shrub zones and tropical deciduous forests. The genus is also common in caves and rock shelters, including deep caves with complete darkness (Valdéz-Mondragón 2008). Hitherto, 31 species of Physocyclus have been described (Platnick 2013). In this paper a new species is described from Mexico.